SYSTEMS THINKING AS A NECESSARY CONDITION FOR EFFICIENT COMPANY MANAGEMENT - HAHARINOV, Oleksii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the issue of systemic thinking as a necessary condition for effective enterprise management. System thinking is the thinking of a modern effective manager of an enterprise. In a general approximation, based on systems theory, thinking systemically means using the system category as a way of looking at an object, situation, process, in this case, an enterprise. Based on this, representatives of enterprise management from the point of view of the development of systems thinking and its application in the process of managing their management object need to understand: the system of elements of the enterprise and how they are related to each other and interact with each other and the external environment; the sequence of functions or activities that it provides; in what the integrity of the enterprise, qualitative determination and purposefulness consists and is expressed. In the subject activity of enterprise management, it is not just knowledge that is important, but rather its systematicity and understanding. And therefore, the authors proposed the following formula: knowledge - understanding - skill - analysis - synthesis - creation. Where the first two stages are necessary as a basis for the formation and development of systemic thinking in the management of the enterprise to ensure its efficiency, and the third stage with a further transition to analysis, in particular, for effective management of the business entity's functioning process. Using the first two stages of this formula, the authors proposed a model for evaluating the integrated level of system thinking of a company management representative, which includes twelve equivalent, from the point of view of systemic significance, differentiated parameters: knowledge and understanding of system concepts and categories; knowledge and understanding, ideologies, purposes and strategies of organizations; knowledge and understanding of the system-forming factor of organizations; knowledge and understanding of system properties; knowledge and understanding of system principles; knowledge and understanding of system patterns; knowledge and understanding of system methods, models, tools, etc.; knowledge and understanding of systemic diseases of organizations; knowledge and understanding of the nature of systemic disasters in organizations; knowledge and understanding of system properties of people; knowledge and understanding of the organization's internal structure and its interaction with the external environment; knowledge and understanding of system potential and key provisions of a system-perfect organization.
Keywords: enterprise; organization; system thinking; system approach; enterprise management; efficiency